The strategy of conflict of interpretations in the poem (dream of an empty night) by the poet Ahmed Abdel Moaty Hijaz - Hayani, Mahmoud Khalif Khudair Obaid (Arab Journal for Sciences and Research Publishing, 2019)
There is no doubt that the interpretive experience is the experience of meaning, and connotations, each approach to the creative text, suggests several readings start from an interpretive strategy through which the text interacts with the interpreter; so that some kind of agreement on meaning or fusion of horizons, and according to this agreement or fusion of horizons there is an understanding of the self Since the text is a lazy machine that always needs a new reading that works to stimulate the text, and produce new meanings, it is based on a conflict between the different meanings and connotations, and can not be said to be the last reading. Of meaning now In the light of these conflicts of interpretation, we have chosen a poem by the poet Ahmed Abdel Moaty Hijaz, and whenever we approach the text proposes a new meaning, the poem revolves in the orbit of a variety of meanings including loss, depression, weakness and strength , Love, dimension, alienation, immigration, immobility, change, etc. The meanings opened by the hermeneutic experience are a struggle for different endless interpretations, because the hermeneutic language focuses on various intentions (author, text, and administrator), but what maintains its continent is Text strategy, semantic field boundaries for each word or phrase in Poem.
Keywords: The conflict of interpretations; The intentionality of the text; The fusion of horizons; Immaturity